Current knowledge about the social wasps (Hymenoptera: Vespidae) in the state of Piauí, Brazil - Rocha, Agda Alves da; Silveira, Orlando Tobias (EntomoBrasilis, 2014)
New records of social wasps in the State of Piauí are presented, contributing to an increased knowledge of this group in this poorly studied region. This study documents new occurrence records for 12 social wasp species and extends their distribution. Atualização do Conhecimento Sobre Vespas Sociais (Hymenoptera: Vespidae) no Estado do Piauí, Brasil Resumo. São apresentados novos registros da fauna de vespas sociais em localidades do Piauí, contribuindo para o aumento do conhecimento desse grupo de organismos na região. Este estudo registra a ocorrência de 12 novos registros de vespas sociais, ampliando suas distribuições.